Ocena możliwości gospodarczego wykorzystania odpadów organicznych i roślin uprawianych na zanieczyszczonych glebach Środkowego Nadodrza = Posiibility estimation of organic wastes and plant products management from the polluted areas of Middle-Odra Land - Greinert, Andrzej; Greinert, Henryk (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Middle Odra Land this one of Polish regions, which being in considerable degree afforested, they possess still the large surface of fallows and the fallow lands, also on soils the good classes. These in turn are partly defective with point of sight of chemism (the dirt, mainly with heavy metals and more seldom the derivatives of petroleum). This shows on searches necessity for these terrains of sensible way of the use implements.
Keywords: 4 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: rekultywacja terenów zdegradowanych" (28-29.06.2007); odpady organiczne; rośliny przemysłowe; grunty skażone; organic wastes; industrial plants; contaminated grounds